THE PEDAGOGICAL FEATURES OF DEVELOPING PROFESSIONAL COMPETENCE OF FUTURE TEACHERS (European Journal of Interdisciplinary Research and Development, 2025)
This article deals with the concept of professional competence of future teachers, the pedagogical features of its formation and the specific qualities of professional competence.